Icariin Inhibits Intestinal Inflammation of DSS-Induced Colitis Mice Through Modulating Intestinal Flora Abundance and Modulating p-p65/p65 Molecule - Zhang, Haoran; Zhuo, Shixuan; Song, Danni; Wang, Leyao; Gu, Junyi; Ma, Junyan; Gu, Yang; Ji, Minghui; Chen, Meijuan; Guo, Yuanyuan (Turkish Journal of Gastroenterology, 2021)
Background: Ulcerative colitis, as a kind of inflammatory bowel disease (IBD) is characterized by abdominal pain. This study aimed toinvestigate the effect of icariin (ICA) on the intestinal microflora of colitis mice.Methods: Fifteen female C57BL/6 mice were randomly divided into the Control group, dextran sodium sulfate (DSS)-induced colitis(DSS) group, and ICA treatment (DSS+ICA) group. The severity of inflammation in DSS-induced colitis mice was evaluated using diseaseactivity scoring (considering weight-loss percentage, stool-shape change, and stool-bleeding scoring). Pathological changes of miceintestinal tract were evaluated using hematoxylin–eosin (HE) staining. Serum levels of TNF-α and IL-6 were detected with enzyme-linkedimmunosorbent assay. Expressions of p65 and p-p65 (p-p65/p65 ratio) were analyzed using Western blot assay. 16S rDNA sequencingwas used to analyze the abundance and composition of intestinal microflora.Results: Compared with DSS group, ICA significantly improved disease activity (P < .05) and reduced inflammatory damage of colontissues (P < .05) in DSS-induced colitis mice. Compared with the DSS group, mice in the ICA group demonstrated significant weightand colon length (P < .05). ICA significantly inhibited expressions of IL-6 and TNF-α compared to the DSS group (P < .05). p-p65/p65 ratio in the DSS + ICA group was remarkably enhanced compared to the DSS group (P < .05). ICA significantly reduced the proportionand activity of Bacteroides, Helicobacteraceae, Turicibacter, and significantly increased that of beneficial microflora (Lactobacillus,Lachnospiraceae, Akkermansia), so as improved damages of colon tissues.Conclusion: ICA can improve intestinal flora abundance and composition of DSS-induced colitis mice, and inhibit tissue damage andinflammatory response through modulating the p-p65/p65 expression.